Students Anxiety in Speaking English at Second Semester Students of English Department in Nommensen HKBP Medan - Padang, Della Afriani Br; Pakpahan, Carolina; Lestari, Febrika Dwi (ALACRITY : Journal of Education, 2024)
This research aims to investigate students' anxiety in Speaking English at Second Semester Students of English Deparment in Nommensen HKBP University Medan. The objectives of this research are (1) to identify the factors or situations that make the students’ feel anxious when they are speak English and (2) to find out and describe the strategies to minimize anxiety for the student.The researcher used descriptive qualitative method, with phenomenology approach. The participants in this research were 25 students in 1 class. The instrument of the collecting data interview and questionnaire. Both of them were conducted online. The researcher gave several questions and questionnaires to be answered by students via Google Forms, and from the students' answers, the researcher saw that the students felt uncomfortable when speaking English, so that from this discomfort, a feeling of anxiety arose when they spoke English. The result of the research showed in two factors, they are internal factors (shyness, lack of self -confident, and fear of making mistakes, and the external factors (lack of preparation, limited vocabulary, and friends/classmates). And there were five strategies to minimize anxiety when speaking english showed in this research (preparation, relaxation, positive thinking, concentration and peer seeking).